Expansions of circulating plasmablasts producing commensal-reactive IgA antibodies are predictors for chronic GVHD - Habenicht, Katharina; Wanzek, Jana; Bootz, Anna; Schäfer, Simon; Vollmer, Lara; Hiergeist, Andreas; Fante, Matthias; Hasenbank, Jakob; Schneider, Andrea; Vasova, Ingrid; Spörl, Silvia; Brandt, Anna; et al. (Blood, 2025)
Chronic graft-versus-host disease (cGVHD) is characterized by dysregulation of the adaptive immune system, including an aberrant B-cell homeostasis after allogeneic hematopoietic stem cell transplantation (allo-SCT). It is uncertain, however, whether this B-cell dysregulation is a result of manifest cGVHD or develops as a sign of aberrant B lymphopoiesis after allo-SCT before cGVHD becomes apparent. To gain insight into the development of B-cell dysregulation before the onset of cGVHD, we analyzed B-cell subpopulations by multiparameter flow cytometry on days 90, 180, and 356 after allo-SCT in a prospective study design. After completion of follow-up, patients were assigned retrospectively to 3 groups according to onset of GVHD: (1) no GVHD (n = 17); (2) acute GVHD (aGVHD) without subsequent cGVHD (n = 32); and (3) cGVHD (n = 59). Although CD21lowCD11c+ B cells were increased in all groups, the frequency of CD20–CD38hi plasmablasts was significantly elevated already 90 days after allo-SCT in patients who subsequently developed cGVHD, compared to patients without GVHD or with aGVHD only (median of CD19+ cells, 5.9% vs 2.2% vs 2.2%; P = .0016 and .0304, respectively). Detailed molecular analysis of expanded plasmablasts revealed a dominance of the immunoglobulin A isotype, with molecular evidence for recent generation in mucosal sites and markers for intestinal homing. A large fraction of the clonally expanded plasmablasts produced antibodies that bound to subgroups of commensals known to produce short-chain fatty acids. In summary, our data suggest that dysregulated intestinal antibody responses against commensals contribute to the pathophysiology of cGVHD.
CRIS-Team Scopus Importer:2025-05-30